Culturally Appropriate Peer-Led Behavior Support Program for African Americans With Type 2 Diabetes - Okoro, Florence O.; Veri, Shelby; Davis, Valencia (Frontiers in Public Health, 2018)
Current literature poorly defines the specific ways trained peer supporter influences the health care behaviors. This study attempts to identify the key defining features of a culturally appropriate peer support program for African Americans with type 2 diabetes by exploring participants experiences related to assistance with daily disease management, emotional support, linkage to clinic care and community resources, and ongoing support. We used a qualitative interpretive descriptive approach to gather data through semi-structured interviews from 20 African Americans with type 2 diabetes participating in a peer support program. Interviews captured participants’ background and experiences with the peer supporter and evaluated the cultural appropriateness of the peer support intervention. Data was coded deductively using predetermined codes found in the peer support literature and inductively to identify emergent themes. Three specific themes were identified namely [1] healthy behaviors [2] frequent telephonic contact and [3] emotional support as a by-product of other support activities. These findings mirror the broader literature on what constitutes culturally appropriate peer support programs for ethnic minorities. We recommend the inclusion of culturally appropriate peer support program to complement diabetes management as a targeted plan for improvement in clinical care and ultimately, diabetes outcome.